Fecundity and reproductive output of the caridean shrimp Periclimenes paivai associated with scyphozoan jellyfish - Rocha de Moraes, Isabela Ribeiro [UNESP]; Wolf, Milena Regina [UNESP]; Lemos Goncalves, Geslaine Rafaela [UNESP]; Castilho, Antonio Leao [UNESP] (Taylor & Francis Ltd, 2017)
Periclimenes paivai is notable for its symbiotic lifestyle with jellyfish. The objective of this study was to investigate the fecundity and reproductive output of females, and specifically to determine whether females protected in their host have a greater reproductive success than other shrimp species. All anatomical parts of the medusae were analyzed and the P. paivai individuals were separated. Among 83 females analyzed, 65 presented embryos in the first developmental stage, and 18 were in the final stage of development. The mean fecundity was 229.08 +/- 120.04 in initial-stage embryos and 191 +/- 114.76 in final-stage embryos. We observed a positive relationship between the embryo number and the female size; however, the embryo number was not related to the embryonic stage, which indicates that females did not lose their embryos during the incubation period. The weight of brood mass during production is closely related to the female weight according to the results of linear regression, as fecundity increased with female size. In its symbiosis, P. paivai can increase the amount of energy used to produce embryos (mean reproductive output = 10.38%) and can elevate the reproductive success.
Keywords: Reproductive biology; medusae; symbiosis; Palaemonidae